Study on positive psychology from 1999 to 2021: A bibliometric analysis - Wang, Feifei; Guo, Jia; Yang, Guoyu (Frontiers in Psychology, 2023)
Objective Positive psychology is a revolution in the science of psychology as well as a new milestone in the development of human society. The purpose of the study was to use bibliometrics and visual analysis to assess the current state and trends in positive psychology research. Methods The Web of Science Core Collection was searched for 4,378 papers on positive psychology between 1999 and 2021. The features of positive psychology research were analyzed using Microsoft Excel 2013, VOSviewer (1.6.17), and CiteSpace (5.8.R1). Results The findings demonstrate a steady growth in positive psychology publications from 1999 to 2021. The United States (1,780) and Harvard University (104), respectively, were the most productive nations and organizations in this subject. Frontiers in Psychology was the most productive journal (288), while the Journal of Personality and Social Psychology had the most co-citations (8,469). Seligman was the most influential author, with 3,350 citations and 5,020 co-citations. The top ten co-cited references, in terms of citation explosion, suggesting that these papers provide the foundation for the growth of this discipline. The systematic review, character strengths, positive psychology intervention, language pleasure, and the COVID-19 pandemic are the focal points of research and development developments in this discipline. Conclusion These findings have helped researchers in positive psychology find new ways to collaborate with partners, hot topics, and research frontiers.